2019
DOI: 10.3390/s19030513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gait Strategy and Speed on Regularity of Locomotion Assessed in Healthy Subjects Using a Multi-Sensor Method

Abstract: The regularity of pseudo-periodic human movements, including locomotion, can be assessed by autocorrelation analysis of measurements using inertial sensors. Though sensors are generally placed on the trunk or pelvis, movement regularity can be assessed at any body location. Pathological factors are expected to reduce regularity either globally or on specific anatomical subparts. However, other non-pathological factors, including gait strategy (walking and running) and speed, modulate locomotion regularity, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…To date, there is no consensus on the optimal position to place the sensors for analysis of STS and other movements, and the optimal position might depend on the purpose of the movement being investigated. For example, it has been reported that movement regularity during walking and running was highest with a sensor located around the seventh cervical vertebra in comparison to a pelvic placement [ 33 ]. Linderman et al, [ 26 ] have also suggested that a sensor located at the head level could provide better kinematic information of the risk of falls in comparison to sensors located at the hip and the trunk.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no consensus on the optimal position to place the sensors for analysis of STS and other movements, and the optimal position might depend on the purpose of the movement being investigated. For example, it has been reported that movement regularity during walking and running was highest with a sensor located around the seventh cervical vertebra in comparison to a pelvic placement [ 33 ]. Linderman et al, [ 26 ] have also suggested that a sensor located at the head level could provide better kinematic information of the risk of falls in comparison to sensors located at the hip and the trunk.…”
Section: Introductionmentioning
confidence: 99%
“…These include an understanding of which output is more robust to testing site characteristics (e.g., corridor lengths, lightening, noise, etc. ), adopted measuring instruments and their configuration (e.g., brand, location on the body, sampling frequency) [35][36][37], type of gait test (e.g., a single pass, a 1-minute or a 6MWT), or instructions given to patients (e.g., self-selected or fast walking speed, use or not use of an assistive device) [28,[38][39][40][41][42][43][44][45]. All these aspects are particularly difficult to standardise in a busy clinical environment and most likely occur in combination with each other.…”
Section: Introductionmentioning
confidence: 99%
“…The intra-subject analysis of the gait variability was defined on the one hand using the CV (the ratio of standard deviation and mean) for stride time and stride length, and on the other hand by regularity of locomotion calculation, based on the autocorrelation analysis of the acceleration module (norm of the acceleration vector) ( 54 ). To register gait speed at steady state walking—a fundamental requisite for calculating valid variability and regularity—the first and the last 2 meters were excluded from the data analysis.…”
Section: Methodsmentioning
confidence: 99%